Flipping the Technical and Vocational Classroom for Increased Instructional Outcomes - Mupita, Jonah; Abdullah, Ade Gafar; BÃ¼nning, Frank (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2020)
Higher learning institutions are under immense pressure to evolve within the realms of the fourth industrial revolution. Training institutions are anticipated to minimize learning costs in the face of increasing enrolments. The flipped classroom model is a suitable instructional pedagogy to achieve institutional goals considering the current ubiquitousness of information and communication technology. The systematic review was aimed at summarizing and identifying research gaps that help inform future research trajectories. The 3-step review process was composed of articles searching and retrieval, filtering and sorting, and final inclusion. Identified empirical articles were; i.) Retrieved and summarized on the basis of tittles, abstracts, methods and basic findings, ii.) Filtered and sorted on the basis of study discipline, and iii.) Synthesized on the basis of basic findings. It was found that the flipped classroom improved academic performance to a limited extent. Most articles unanimously concurred that the flipped classroom model makes learning enjoyable and enables the development of lower order cognitive skills outside class and higher order cognitive skills through F2F (face to face) active learning. The success of the model in higher education is hinged on excellent planning, implementation and evaluation.